Identification of the Potential Quartz Sandstone in the Sambong Area By the Dipole-Dipole Configuration of Resistivity Method - Subhan Arif; Nurul Dzakiya; Samuel Kristiyana; Rohmad Bagus Abadi (Politeknik Negeri Batam, 2023)
The presence of quartz sandstone outcrops in the southeast of the study site suggests the presence of quartz sandstones in the northwest, according to the strike direction. This geoelectrical measurement aims to determine the distribution of these sandstones below the surface. The method used is geoelectric with a dipole dipole configuration. Measurements were made on four track lines. Tracks A and B indicate the existence of a layer of sandstone below the surface. Tracks C and D do not show any layers of quartz sandstone. This is caused by the presence of faults or folds that cause the layer to shift from the previously predicted path.